Monitoring of Sun’s Uv Radiation and Stratospheric Ozone Layer Thickness over the Region of Novi Sad (Serbia) - Mijatović, Zoran; Kobilarov, R. Kobilarov; Vujičić, B. T.; Mihailović, D. T. (Journal of Economic Development, Environment and People, 2013)
The results of the Sun’s UV radiation and stratospheric ozone layer thickness over the region of Novi Sad (Serbia) are reported. Monitoring the UV radiation and stratospheric ozone layer thickness started in 2003 and 2007 respectively. Results recorded during these years have been analyzed. Upon these analyses it can be concluded that during observational period, the significant difference in daily maxima of the UV radiation recordings or ozone seasonal maximal values from year to year, has not been detected. Obtained results are graphically depicted.